Integrating of Anatomy and Physiology courses in basic medical sciences (case study in Mashhad Faculty of Medicine) - Atena Gerivani; Tooraj Sadeghi; Hossein Karimi Moonaghi; Ahmad Zendedel (Mashhad University of Medical Sciences, 2020)
Background: The aim of this study is to organize the educational materials of basic medical sciences by integrating anatomy and physiology courses in Mashhad University of Medical Sciences. Methods: This is a descriptive cross-sectional study focusing on the views of professors and students of the basic medical sciences in February 2018 and September 2018 in Mashhad University of Medical Sciences, on the presentation of anatomy and physiology courses in the form of system organ and integration. 241 students, who passed their lessons as Integrated, were selected by simple random sampling method. The study instrument was a researcher-made questionnaire that its face validity has been used for validity. Results: The average of the professors' opinions about integrated teaching indicated that according to the sign test, which is related to non-parametric statistics, the median of 2.893 with a standard deviation of 0.52 was obtained, so the results of the professors' views were significantly higher than the median score. Also, according to the results of students, the statistical number of T was 5.287 and the significance level was assigned less than 0.05. Conclusion: Overall, according to opinions of professors and students of Mashhad University of Medical Sciences, it can be said that their satisfaction with the integration of basic medical sciences lessons in anatomy and physiology is above average.